PENGARUH HARGA DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA CV. MAKMUR JAYA ABADI (MJA) BIMA - Fahri Kusumahardi; Ernawati, Sri (Lembaga Pengembangan Kinerja Dosen, 2022)
Competition in the business world is getting tighter, marked by the emergence of new products with various kinds of offers in the market, companies must have the right marketing strategy in facing competition. Price and distribution channels are important factors to win a competition in marketing products, namely distribution, where with the implementation of the right distribution channels, the company's products can be known and reach consumers in the right amount and time. The purpose of this study to determine the price and distribution channels have a positive and significant effect partially or simultaneously on sales volume at CV. Makmur Jaya Abadi (MJA) Bima. The research method used in this study is the Associative research method The population in this study is an outlet that sells Unilever products in Cv. Makmur Jaya Abadi (MJA) Bima. The sample is taken in accordance is 50 people, where this study concludes that there are 50 outlets. Data Analysis Techniques using Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Test Analysis, Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) The results of the discussion show that the price has a significant effect on sales volume at CV. Makmur Jaya Abadi (MJA) Bima, distribution channels have no positive and partial effect on sales volume at CV. Makmur Jaya Abadi (MJA) Bima. And prices and distribution channels have a significant effect on sales volume at CV. Makmur Jaya Abadi (MJA) Bima